MICROMORPHOMETRIC CHANGES OCCURRING IN SPLEEN TISSUE DURING POLYPRAGMASY - Saidov A.A. (Central Asian Journal of Medicine, 2025)
In this scientific study, the morphometric characteristics of splenic lymphoid tissue in white outbred rats from experimental and control groups aged 3, 6, and 10 months were examined. The organometric parameters of the spleen - length, width, thickness, weight, and surface area - were determined, and their average values were calculated for each age group. Additionally, micromorphometric parameters of the white pulp were analyzed using microscopic methods, including the average surface area and diameter of lymphoid nodules (LN), the area of the periarterial lymphoid sheath (PALS), the surface areas of the mantle and marginal zones, and the diameter of germinal centers. The obtained results allowed for the identification of age-related morphological changes and provided an important scientific basis for assessing the developmental dynamics of lymphoid tissue in the rat organism.